Future semiochemical control of codling moth, Cydia pomonella - Whitfield, E. Charles; Fountain, Michelle T. (Frontiers in Horticulture, 2024)
Codling moth (CM), Cydia pomonella, is a significant pest of apple (Malus domestica) and other orchard crops worldwide, posing challenges due to the decrease in registered insecticides, rising resistance, and a changing climate. The pest exhibits a strong resistance capacity to both synthetic and natural insecticides, while shifting seasonal temperatures disrupt the reliability of phenology-temperature models for predicting targeted control strategies. Alternative control strategies are necessary to future-proof control of this pest. Current control methods primarily rely on chemical insecticide sprays or granulosis virus applications during egg hatching. This review focuses explicitly on semiochemical-based manipulation of CM adults and larvae for control in orchards. Topics covered include the role of semiochemicals in integrated pest management, area-wide control, mating disruption, female attractants, larval kairomones, and incorporation into monitoring and control strategies. The potential of CM repellents in a push–pull strategy is also discussed. Primary sources for identifying relevant literature included GoogleScholar and ResearchGate, with a focus on papers published since 2013 but also include relevant papers from 2003. Nine review papers and 119 papers were reviewed. The review emphasizes that effective control necessitates an area-wide approach targeting all life stages (eggs, larvae, pupae, and adults). Comprehensive monitoring is crucial for identifying CM “hot-spots” and enhancing targeted interventions. Growers must consider landscape context when designing control programs. Lastly, recommendations are provided for future research and CM management strategies. There are opportunities to explore and exploit female kairomone attractants and repellents in control strategies and modify monitoring traps to be more attractive and autonomous.